Implementasi Terapi Senam Anti Hipertensi dan Pemberian Buah Semangka Untuk Menurunkan Tekanan Darah Pada Klien dengan Hipertensi - Nurlaela, Marisah; Safitri, Alfika; Mahasari, Denida; Nurhasanah, Cucu; Noviana, Diana; Herawati, Herti Eka; Rachmawati, Annisa Ena; Yeni, Neng; Aprilia, Sonia; Kulsum, Umi; Mulyani, Utami (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Hypertension is a leading non-communicable disease with high prevalence in Banten Province, particularly in Cipare Subdistrict, Serang City. Low public awareness regarding hypertension management necessitates a community-based educational and promotive intervention. Objective: This program aimed to enhance public knowledge and promote healthy lifestyle behavior in managing hypertension through complementary therapy and health education. Method: Activities involved Community Discussion Forums (MMD I & II) and the implementation of anti-hypertension exercises and watermelontherapy. Blood pressure was monitored through pre-test and post-test evaluations. Result: Of the 25 participants, 12 demonstrated reduced blood pressure following the intervention. Knowledge about hypertension improved significantly, and the community agreed to conduct hypertension exercises routinely, led by trained health volunteers. Conclusion: Community- based interventions using healthy exercise and watermelon therapy effectively reducedblood pressure and promoted health awareness. This approach can serve as a sustainable model for hypertension management at the community level.